What Sustainable Development Goals Do Social Innovations Address? A Systematic Review and Content Analysis of Social Innovation Literature - Eichler, Georg M.; Schwarz, Erich J. (Sustainability, 2019)
Interest in social innovations (SIs) from both the academic and the policy side is growing. Nonetheless, we still know little about which sustainable development goals (SDGs) SIs already address. Furthermore, only little is known about who the innovators developing and implementing SIs are. In this paper, we aim to bring more clarity and structure to the field of SIs. Firstly, a systematic literature review was conducted, before a content analysis was used to analyze the definitions used with regard to similarities. Secondly, all case studies described in the reviewed articles were then further systematically analyzed in order to identify the social or environmental problems addressed and the innovators involved. For the purpose of classifying the diverse types of problems, we used the globally known and broadly accepted 17 sustainable development goals (SDGs). Results showed that most SI case studies deal with an improvement of health and well-being. Furthermore, our study illustrates that there is a pronounced difference in the focus of SIs between developing and developed countries. Concerning the innovators, our results indicate that five types of innovators are fundamentally involved in developing and implementing SIs: social entrepreneurs, NGOs and non-profits, public institutions, civil society, firms, and social enterprises. Our definition analysis as well as the identification and classification of the innovators and addressed social needs bring much-needed clarity and structure to the field. However, our systematic review shows that SI is still in its infancy and it will be interesting to see where the field will head.
Keywords: Innovation sociale; Objectifs de développement durable; Social entrepreneurship; systematic review